GE_GERICHTE P/26309/2017 vom 9. Juni 2021 - GE Cour de justice (2021)
PRINCIPE DE L'ACCUSATION;VIOLATION D'UNE OBLIGATION D'ENTRETIEN;IN DUBIO PRO REO;PRÉSOMPTION D'INNOCENCE | CP.217; CPP.9; CPP.10.al3; CPP.136.al2.letb; CPP.325.al1; CPP.329.al2; CPP.350.al1